Optimal perfusion chemotherapy: A prospective comparison of mitomycin C and oxaliplatin for hyperthermic intraperitoneal chemotherapy in metastatic colon cancer. Issue 8 (1st April 2020) - Woeste, Matthew R.; Philips, Prejesh; Egger, Michael E.; Scoggins, Charles R.; McMasters, Kelly M.; Martin, Robert C. G.
Abstract: Background: Peritoneal carcinomatosis of colorectal adenocarcinoma (CRC) origin is common and is the second‐most frequent cause of death in colorectal cancer. There is survival benefit to surgical resection plus hyperthermic intraperitoneal chemotherapy (HIPEC) for patients with metastatic CRC. However, there remains controversy between oxaliplatin (Oxali) and mitomycin C (MMC), as the agent of choice. Methods: A review of our 285 patients prospective HIPEC database from July 2007 to May 2018 identified 48 patients who underwent cytoreductive surgery plus HIPEC with MMC or Oxali. Patients were stratified based on preoperative and postoperative peritoneal cancer indices (PCI). The primary outcomes of survival and progression‐free survival were compared. Results: Type of HIPEC chemotherapy was not found to be predictive of overall survival. Preoperative PCI ( P  = .04), preoperative response to chemotherapy ( P  = .0001), and postoperative PCI ( P  = .05) were predictive for overall survival. Conclusions: MMC or Oxali based HIPEC chemotherapy are both safe and effective for the management of peritoneal only metastatic CRC. Both perfusion therapies should be considered with all patients receiving modern induction chemotherapy.